A proteotranscriptomic study of silk-producing glands from the orb-weaving spiders - Aparecido dos Santos-Pinto, Jose Roberto [UNESP]; Esteves, Franciele Grego [UNESP]; Sialana, Fernando J.; Ferro, Milene [UNESP]; Smidak, Roman; Rares, Lucaciu Calin; Nussbaumer, Thomas; Rattei, Thomas; Bilban, Martin; Bacci Junior, Mauricio [UNESP]; Palma, Mario Sergio [UNESP]; Luebec, Gert (Royal Soc Chemistry, 2019)
Orb-weaving spiders can produce different silk fibers, which constitute outstanding materials characterized by their high strength and elasticity. Researchers have tried to reproduce the fibers of these proteins synthetically and/or by using recombinant DNA technology, but only a few of the natural physicochemical and biophysical properties have been obtained to date. Female orb-web-spiders present seven silk-glands, which synthesize the spidroins and a series of other proteins, which interact with the spidroins, resulting in silk fibers with notable physicochemical properties. Despite the recognized importance of the silk-glands for understanding how the fibers are produced and processed, the investigation of these glands is at a nascent stage. In the current study we present the assembled transcriptome of silk-producing glands from the orb-weaving spider Nephila clavipes, as well as develop a large-scale proteomic approach for in-depth analyses of silk-producing glands. The present investigation revealed an extensive repertoire of hitherto undescribed proteins involved in silk secretion and processing, such as prevention of degradation during the silk spinning process, transportation, protection against proteolytic autolysis and against oxidative stress, molecular folding and stabilization, and post-translational modifications. Comparative phylogenomic-level evolutionary analyses revealed orthologous genes among three groups of silk-producing organisms - (i) Araneomorphae spiders, (ii) Mygalomorphae spiders, and (iii) silk-producing insects. A common orthologous gene, which was annotated as silk gland factor-3 is present among all species analysed. This protein belongs to a transcription factor family, that is important and related to the development of the silk apparatus synthesis in the silk glands of silk-producing arthropods.